Buckling of orthotropic plates with bimoments - M.K. Usarov (Инженерно-строительный журнал, 2015)
The paper is dedicated to improvement of plate theory in order to take into account forces, moments and bimoments, generated by nonlinear law of displacement distribution in plate cross-sections. Integral correlations for defining forces, moments and bimoments were given.